2014
DOI: 10.1007/s40618-014-0230-2
|View full text |Cite
|
Sign up to set email alerts
|

Prematurity and low birth weight lead to altered bone geometry, strength, and quality in children

Abstract: Children born either prematurely or SGA seem to have smaller and weaker bones. Those born both premature and SGA were the most affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…12,942 singleton infants were born at term (≥37 completed weeks). Premature infants were excluded as prematurity is known to effect skeletal development (13). Length of gestation was estimated from the date of the mother’s last menstrual period.…”
Section: Methodsmentioning
confidence: 99%
“…12,942 singleton infants were born at term (≥37 completed weeks). Premature infants were excluded as prematurity is known to effect skeletal development (13). Length of gestation was estimated from the date of the mother’s last menstrual period.…”
Section: Methodsmentioning
confidence: 99%
“…The adverse effects of LBW on fetuses and newborns may persist throughout the life cycle (25,26). Recent studies have shown that LBW young adults have a higher incidence of short-and long-term dysfunction in several vital organs (27)(28)(29); however, the effect of LBW on the intestinal barrier function of young adults is still not well characterized. In the present study, it was hypothesized that the hindgut epithelial barrier function in LBW pigs was different from the normal BW (NBW) pigs during the growing stage.…”
mentioning
confidence: 99%
“…We predicted that birthweight would be positively associated with all measures of bone strength. Previous studies and meta‐analyses of humans have found that higher mass at birth is significantly correlated with tissue mineral density, bone cross‐sectional robusticity, and even muscle strength (Longhi et al, 2015; Schlüssel et al, 2010). However, we found that birthweight was only significantly associated with two of 36 measures examined: TMD of the fibula and yield moment of the femur (Tables S2 and S6; p ≤ 0.044; Figures 2b,‐c).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, low birthweight had been shown to independently be associated with compromised motor development (Boonzaaijer et al, 2021;de Kieviet et al, 2009;Pitcher et al, 2011) and low bone tissue mineral density, robusticity, and strength (Longhi et al, 2015).…”
mentioning
confidence: 99%